Risk and protective factors for non communicable diseases in the Belo Horizonte population: Vigitel 2008 - Bruna Mara Duarte; Regina Tomie Ivata Bernal; Deborah Carvalho Malta (Revista Brasileira de Epidemiologia, 2013)
Introduction: The Non Communicable Diseases (NCD) are the main causes of death in, having known, avoidable the Risk Factor (RF) and susceptible to intervention. Objective: Identify the prevalence of RF and protection for NCD in the Belo Horizonte, 2008. Methodology: Data were analyzed from Vigitel, in Belo Horizonte, 2008. They are presented to the frequencies of RF according to gender, schooling, and calculated the p-value and the PR. Results: Men showed more frequencie in the following RF: higher consumption of meat and milk with fats, soft drinks, abusive consumption of alcohol, drive after drinking, ex-smokers. Men presented in relation to protective factors statistically significant differences in consumption of beans and leisure-time physical activity. Women had the highest frequencies in the consumption of fruits and vegetables, protection against ultraviolet radiation, self-assessment of health as poor, and declared more morbidities such as: arterial hypertension, dyslipidemia, asthma and osteoporosis. Adults with low levels of education compared with high education (reference) presented the following PR: smoke PR 2.09 (95%CI 1.43 - 3.05); consumption of 20 cigarettes and more PR 2.54 (95%CI 1.19 - 5.43); overweight PR 1.27 (95%CI 1.02 - 1.56); obesity PR 1.6 (95%CI 1.04 - 2.47); consumption of soft drinks PR 2,07 (95%CI 1.51 - 2.83); consumption of fruit and vegetable intake PR 0.53 (95%CI 0.40 - 0.72); consumption of beans PR 1.15 (95%CI 1.05 - 1.27); watch TV PR 1.33 (95%CI 1.00 - 1.77); driving after alcohol consumption PR 0.14 (95%CI 0.04 - 0.53); hypertension PR 1.75 (95%CI 1.37 - 2.24); diabetes PR 2.24 (95%CI 1.23 - 4.09). Conclusion: The telephone surveys are an important method to monitor the distribution of risk and protective factors in the population and to permit to orient health promotion programs and prevention.